2021
DOI: 10.3389/fped.2021.727411
|View full text |Cite
|
Sign up to set email alerts
|

Kikuchi-Fujimoto Disease With Encephalopathy in Children: Case Reports and Literature Review

Abstract: Background: Kikuchi-Fujimoto disease (KFD) is a benign and self-limiting disease characterized by regional lymphadenitis and low-grade fever. Encephalopathy may present in children with KFD. We present three cases of KFD with encephalopathy in children and a literature review.Methods: Literature published between 2010 and 2020 was reviewed to understand the clinical features, laboratory findings, and treatments for encephalopathy occurring in children with KFD.Results: The interval between KFD and onset of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Nineteen pediatric patients were identified, including two patients we presented (Table 1). 2,4–13 Eight patients were males and eleven patients were females. The onset age ranges from 6 to 18 years (the median age was 14 and the interquartile range was 9–16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nineteen pediatric patients were identified, including two patients we presented (Table 1). 2,4–13 Eight patients were males and eleven patients were females. The onset age ranges from 6 to 18 years (the median age was 14 and the interquartile range was 9–16).…”
Section: Resultsmentioning
confidence: 99%
“…2,[4][5][6][7][8][9][10][11][12][13] Eight patients were males and eleven patients were females. The onset age ranges from 6 to 18 years (the median age was 14 and the interquartile range was 9-16).…”
mentioning
confidence: 99%
“…Encephalopathy in KFD is uncommon. One study found 9 cases reported in children between 2010 and 2020. Another large case series reported an incidence of neurological complications of 4.5% in KFD, most commonly aseptic meningitis.…”
mentioning
confidence: 99%